anonymous
  • anonymous
Solve for x: 4|2x − 2| + 10 = 34
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
a. x = −4, x = 2 b. x = 4, x = −4 c. x = 2, x = −2 d. x = 4, x = −2
anonymous
  • anonymous
B
anonymous
  • anonymous
absolute value there is no negatives

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
@kyle55
anonymous
  • anonymous
could i ask you a few more
anonymous
  • anonymous
of course
anonymous
  • anonymous
Consider the functions f(x) = 3x2 + 1 and g(x) = x + 3. What is the value of f[g(−1)]? Select one: a. 7 b. 37 c. 13 d. 12
anonymous
  • anonymous
I think C
anonymous
  • anonymous
@welshfella
welshfella
  • welshfella
@_greatmath7 please explain how you got that answer
texaschic101
  • texaschic101
4 | 2x - 2 | + 10 = 34 --- subtract 10 4 | 2x - 2 | = 24 -- divide by 4 | 2x - 2 | = 6 2x - 2 = 6 -(2x - 2) = 6 2x = 6 + 2 -2x + 2 = 6 2x = 8 -2x = 6 - 2 x = 4 -2x = 4 x = -2
anonymous
  • anonymous
and for the second one?
texaschic101
  • texaschic101
sorry...not good with functions
welshfella
  • welshfella
you can find f(g(x) first - by replaceing the x in f(x) by g(x)
welshfella
  • welshfella
|dw:1441648906063:dw|
welshfella
  • welshfella
= 3(x + 3)^2 + 1 f(g(-1)) is found by plugging in x = -1 into the above
welshfella
  • welshfella
= 3(-1 + 3)^2 + 1 - can you work that out?
anonymous
  • anonymous
3(1 + 9) 3 + 27 + 1 31
welshfella
  • welshfella
no work out the parantheses first = 3(2)^2 + 1 = 3*4 + 1 = 13
welshfella
  • welshfella
remember PEMDAS - order of operations
welshfella
  • welshfella
the -1 + 3 had to be done first
welshfella
  • welshfella
@hwyl - noswaith da!
hwyl
  • hwyl
da?
hwyl
  • hwyl
niet
welshfella
  • welshfella
oh should it be dda?
hwyl
  • hwyl
it's day time where i am
welshfella
  • welshfella
my welsh is pretty dire....
welshfella
  • welshfella
ok bore da!
hwyl
  • hwyl
@miracrown she knows Welsh and Gaelic
imqwerty
  • imqwerty
:)
welshfella
  • welshfella
that's impressive.
welshfella
  • welshfella
If a remember correctly hwyl means spirit or full of life
Miracrown
  • Miracrown
Her şeyi biliyorum @hwyl @welshfella

Looking for something else?

Not the answer you are looking for? Search for more explanations.